The work of symbolic production of the of employee organizations between 1930-1940 - Sánchez Salcedo, José Fernando (Sociedad y Economía, 2011)
In 1930, arise in Colombia, a set of organizations of employees whose primary purpose was to obtain by the government, the recognition of a package of measures to ensure the exercise of their functions. The emergence of these organizations, told from the beginning with the endorsement of the newspaper El Tiempo, was accompanied by a production of process symbolic geared to justify their political actions (congresses, mobilizations, etc), but above all to define its status as union belonging to the middle classes.